(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
Task-Based Language Teaching (TBLT) has gained increasing recognition as an effective pedagogical approach within English as a Foreign Language (EFL) contexts. Grounded in communicative language teaching and second language acquisition theory, TBLT emphasizes the use of meaningful tasks to promote authentic language use. This article examines the effectiveness of TBLT in EFL settings by exploring its theoretical foundations, reviewing empirical research on learner outcomes, and analyzing challenges related to implementation. Particular attention is given to its impact on communicative competence, learner motivation, and classroom interaction. The discussion also highlights the importance of contextual adaptation and pedagogical support. The article concludes that, despite certain limitations, Task-Based Language Teaching offers a flexible and future-oriented framework capable of addressing the communicative needs of EFL learners when appropriately implemented.